The complete mitochondrial genome of Cleithenes herzenstein and its phylogenetic analysis. (2nd September 2016) - Bo, Zhang; Wenping, Song; Kefeng, Liu; Debin, Zheng; Chao, Ma; Guangxia, Xiao
Abstract: The complete mitochondrial genome of Stewartia sinensis was obtained with long PCR approach. Amplification primers were designed according to mitogenome sequences of some other fish species. PCR reactions were according to Kong et al. (2009 ). The complete mitochondria sequence of Cleithenes herzenstein was deposited in GenBank under the accession number KT223828. Structural and evolutionary analyses were also performed. The length of the complete mitochondrial DNA sequence was 17 175 bp, consisting of 13 protein-coding genes, 22 tRNA genes, and two rRNA genes. Other than D-loop, another non-coding region named ''OL'' region was found (Table 1 ). The ''OL'' region (CTTTTTCCCGCCTAGTTTAACCAGTAAAAGGCGGGAA) is 38 bp and has the potential to fold into a stem-loop secondary structure. Most of the genes were encoded on the heavy strand (H strand) except for ND6 and eight tRNA genes (Table 1 ). The base composition and gene arrangement of C. herzenstein mitogenome was identical to typical vertebrate. For sequence alignment, the mitogenome sequence of C. herzenstein was 96% and 95% similar to that of Platichthys stellatus and Verasper moseri, respectively.